Creep Behaviour in Cracked Sections of Fibre Reinforced Concrete Proceedings of the International RILEM Workshop FRC-CREEP 2016 - Serna, Pedro; Llano-Torre, Aitor; Cavalaro, Sergio H. P. (RILEM Bookseries,, 2017)
This is the first publication ever focusing strictly on the creep behaviour in cracked sections of Fibre Reinforced Concrete (FRC). These proceedings contain the latest scientific papers about new testing methodologies, results and conclusions of multiple experimental campaigns and recommendations about significant factors of long-term behaviour, experiences from more than ten years of creep testing and some reflections about future perspectives on this topic. This book is an essential reference for all researchers of creep behaviour on FRC. This volume is the result of the efforts of the RILEM TC 261-CCF, that has been working since 2014 to develop standardized methodologies and guidelines to compare results from different laboratories and get a better understanding of the significant parameters related to creep of FRC.